2017
DOI: 10.1080/09593330.2017.1305001
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater nutrient removal in a mixed microalgae–bacteria culture: effect of light and temperature on the microalgae–bacteria competition

Abstract: The aim of this study was to evaluate the effect of light intensity and temperature on nutrient removal and biomass productivity in a microalgae-bacteria culture and their effects on the microalgae-bacteria competition. Three experiments were carried out at constant temperature and various light intensities: 40, 85 and 125 µE m s. Other two experiments were carried out at variable temperatures: 23 ± 2°C and 28 ± 2°C at light intensity of 85 and 125 µE m s, respectively. The photobioreactor was fed by the efflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(35 citation statements)
references
References 39 publications
1
32
0
2
Order By: Relevance
“…It must be noted that the differences in the ammonium consumption were not significant between R-A and R-B, even during Assay A3, where nitrification rate was the highest (Table A. 4). Hence, the lower microalgae activity in R-A had to be compensated with the AOB activity so that both R-A and R-B had similar ammonium recovery rates.…”
Section: Discussionmentioning
confidence: 92%
“…It must be noted that the differences in the ammonium consumption were not significant between R-A and R-B, even during Assay A3, where nitrification rate was the highest (Table A. 4). Hence, the lower microalgae activity in R-A had to be compensated with the AOB activity so that both R-A and R-B had similar ammonium recovery rates.…”
Section: Discussionmentioning
confidence: 92%
“…The phototrophic culture was dominated by Scenedesmus spp. according to González-Camejo et al [18]. Microalgae were concentrated with a cross-flow ultrafiltration hollow-fibre system (5.7-11.7 gVSS•L -1 ).…”
Section: Thermophilic Reactor Performancementioning
confidence: 99%
“…Great phylogenetic differences were observed in growth rate, nutrient removal capacity and preferred habitat among microbial groups (Beuckels et al, 2015;González-Camejo et al, 2017). Liu and Vyverman (2015) reported that the filamentous microalgae Cladophora sp., Klebsormidium sp.…”
Section: Microorganism Selection and Consortium Constructionmentioning
confidence: 99%